Effect of active learning techniques on students’ choice of approach to learning in Dentistry: A South African case study - Khan, S (South African Journal of Higher Education, 2011)
The purpose of this article is to report on empirical work, related to a techniques module, undertaken with the dental students of the University of the Western Cape, South Africa. I will relate how a range of different active learning techniques (tutorials; question papers and mock tests) assisted students to adopt a deep approach to learning in this large diverse group of students. They then completed an adapted version of the revised study process questionnaire which focussed on the effects of these active learning techniques and how these learning techniques assisted with a change in approach to learning adopted by them. Results indicated that the active learning techniques led to a better understanding of the concepts covered within the module. It also showed how the new exercises guided them to adopt a deep approach to learning. It can be concluded that with this type of educational research, students’ learning difficulties are not just emphasized and highlighted but that these problems are also understood. This research also guided the educator to search for practical solutions to these observed difficulties.